Planowanie i wybór sekwencji montażu we współbieżnym projektowaniu elementów i zespołów maszyn - Sąsiadek, Michał
In the doctoral dissertation a new method of assembly sequence planning in the concurrent design is presented. This method enables to generate a set of possible assembly sequence of complex product and its evaluation according to established criteria. These criteria allow for easy and cheap assembly process. Computer implementation of the method constitutes essential part of the thesis. Application of the computer program is presented on the real life examples. Characteristic feature of the method is its usefulness in the early stages of product design, mainly in the preliminary design. Application of the method contributes to reduction of time and cost of production.
Keywords: planowanie montażu; projektowanie współbieżne; sekwencja montażu; Montaż